Morphological and molecular characterization of Magnaporthe oryzae causing rice blast disease in Odisha - Sahu, Chinmayee; Yadav, Manoj Kumar; Panda, Gayatree; Aravindan, S; Umakanta, Ngangkham; Raghu, S; Prabhukarthikeyan, S R; Keerthana, U; Adak, Totan; Sharma, Vikas; Mohanty, Mihir Ranjan; Rath, P C; et al. (ORYZA-An International Journal of Rice, 2018)
Rice blast disease is one of the most destructive disease causing enormous yield losses to rice in different rice growing regions of the world. The present study aims to identify and characterized the rice blast pathogen Magnaporthe oryzae from different rice growing regions of Odisha. Twenty isolates were collected and categorized into three groups based on colony colour i.e., grayish blackish, grayish and white, and in two group based on the texture of the colony as smooth and rough. Molecular characterization of blast isolates was done with two ITS primers. The sequence analysis of the OD-2 blast isolate showed maximum similarity with Malaysia isolate. In phylogenetic analysis, the blast isolates were grouped into two major clusters. The Odisha isolate (OD-2) along with Chhattisgarh, are in one cluster whereas, blast isolates from China and Japan are in another cluster. Our study showed high degree of morphological and genetic variation among the isolates collected from different locations. The finding of this study would enhance the practical application of research in the field of epidemiology, disease control and developing breeding strategies for blast disease.